(untitled) (Research, Society and Development, 2022)
Startups can play this role due to their dynamism in technological development, innovations that change sectors of the economy and their ability to handle specific and new knowledge. This is reflected in the expansion and diversification of public programs to support startups in different countries, and in the expansion of efforts by large companies to establish connections with innovative startups. The main objective of this work is to explore the growing importance of entrepreneurship in the innovation process of the 21st century. The methodology used was the bibliographic reference where we guided the search for the theme in scientific articles and specialized sites. The study was able to reveal that the Brazilian capital market still needs to advance, as there are few national corporate funds focused on high-risk investments and focused on startups. Obviously, this has to do with the country’s macroeconomic conditions. Interest rates have been very high for many years, which has inhibited venture capital.